Non-linear multi-scale finite element method for prediction of tensile behaviour of carbon nanotube-reinforced polymer composites Nelinearna, viÅ¡eskalna metoda konaÄnih elemenata za predvidanje vlaÄnog ponaÅ¡anja polimernih kompozita ojaÄanih ugljiÄnim nanocijevima - Mohammadpour, E. (University of Split, 2013)
The ability of using carbon nanotubes as the strongest and stiffest elements in nanoscale composites remains a powerful motivation for research in this area. This paper describes a finite element modelling appropriate for the numerical prediction of the mechanical behaviour of polypropylene which is reinforced with single-walled carbon nanotubes. A multi-scale representative volume element is proposed for modelling the tensile behaviour of carbon nanotube reinforced composites. Within the representative volume element, the reinforcement is modelled according to its atomistic microstructure. A model based on the modified Morse interatomic potential is used for simulating the isolated carbon nanotube. In this work, the matrix is modelled as a medium in a form of a continuum by utilizing solid elements and in order to describe its behaviour, an appropriate non-linear material model is adopted. A cohesive zone model is assumed between the nanotube and the matrix with an ideal bonding until the interfacial shear stress exceeds the corresponding strength. By using the representative volume element, a unidirectional nanotube/ polymer composite was modelled and the results were compared to the corresponding rule-of-mixtures predictions. The effect of interfacial shear strength on the tensile behaviour of the nanocomposite was also studied. The influence of adding a single-walled carbon nanotube to the polymer is discussed and the results show that Youngâs modulus and tensile strength of the polymer significantly increase in the presence of carbon nanotubes. Â© 2012, University of Split. All Rights Reserved.